Αvβ3 integrins negatively regulate cellular forces by phosphorylation of its distal NPXY site. (19th December 2016) - Milloud, Rachel; Destaing, Olivier; de Mets, Richard; Bourrin‐Reynard, Ingrid; Oddou, Christiane; Delon, Antoine; Wang, Irène; Albigès‐Rizo, Corinne; Balland, Martial
Abstract : Research article : Artist view of a single Mouse Embryonic Fibroblast αvβ3 integrin knockout stained for talin and vinculin with representative traction vectors exerted by the cell on its micro‐environment. The related study highlights the major role of αvβ3 integrins in the spatial regulation of cellular forces through its ability to modulate its affinity with kindlin . Abstract : Background information: Integrins are key receptors that allow cells to sense and respond to their mechanical environment. Although they bind the same ligand, β1 and β3 integrins have distinct and cooperative roles in mechanotransduction. Results: Using traction force microscopy on unconstrained cells, we show that deleting β3 causes traction forces to increase, whereas the deletion of β1 integrin results in a strong decrease of contractile forces. Consistently, loss of β3 integrin also induces an increase in β1 integrin activation. Using a genetic approach, we identified the phosphorylation of the distal NPXY domain as an essential process for β3 integrin to be able to modulate traction forces. Loss of β3 integrins also impacted cell shape and the spatial distribution of traction forces, by causing forces to be generated closer to the cell edge, and the cell shape. Conclusions: Our results emphasize the role of β3 integrin in spatial distribution of cellular forces. We speculate that, by modulating its affinity with kindlin, β3 integrins may be able to locate near the cell edge where it can control β1 integrin activation and clustering. Significance: Tensional homeostasis at the single cell level is performed by the ability of β3 adhesions to negatively regulate the activation degree and spatial localization of β1 integrins. By combining genetic approaches and new tools to analyze traction distribution and cell morphology on a population of cells we were able to identify the molecular partners involved in cellular forces regulation.